The influence of customer’s purchase decision toward family Takaful product at Etiqa Takaful Berhad / Nurul Hafizah Zaini - Zaini, Nurul Hafizah (2010)
This research was conducted focusing on the influence of customer’s purchase decision toward Family Takaful Product at Etiqa Takaful Berhad, Batu Pahat. From this research, the customer’s purchase decisions were consumer attitude, demographic characteristics and purchase perception. The researcher, will do some survey about this topic. To conduct this research, researcher use 50 potential customers or respondent to answering the question. The question is very important for researcher to get the data needed. The result will be come out through Statistical Package for Social Science (SPSS). Then, the main objective of this research is to identify the level of customer’s purchase decision toward the purchase of Family Takaful product. From this research we can see the level of customer’s purchase decision about the purchase of Family Takaful product. Then, the second objective of this study is to rank which of the customers purchase decisions is more effective to increase the sales or the purchase of Family Takaful product. We can see the result from the finding that come out from using of computer based Statistical Package for Social Science (SPSS) Program version 14.0. The last objective from this study is to provide some recommendation on how to increase the sales of Family Takaful product toward customer’s purchase decision about family Takaful product.